Use of subcutaneous ureteral bypass systems as a bridge to definitive ureteral repair in a cat with bilateral ureteral ligation secondary to complicated ovariohysterectomy. Issue 2 (23rd May 2019) - Beer, Andrew James Carey; Lipscomb, Vicky J; Rutherford, Lynda; Lee, Karla Chui Luan
Abstract : A kitten presented with acute kidney injury, bilateral hydronephrosis and proximal hydroureter, three days following bilateral ureteral ligation, during a complicated ovariohysterectomy procedure. Clinical signs were anorexia, lethargy, weakness, hypothermia, nausea, pain and anuria, associated with marked azotaemia, hyperkalaemia and metabolic acidosis. Insufficient response to medical management alone led to emergency surgical placement of bilateral subcutaneous ureteral bypass (SUB) systems, resulting in dramatic improvement in azotaemia and acidosis and resolution of hyperkalaemia. Elective bilateral neoureterocystostomy was performed the next day. The cat was clinically well for three months until the left SUB cystostomy catheter migrated out of the bladder resulting in uroabdomen. At this time, fluoroscopy demonstrated normal ureteral function bilaterally, so both SUBs were removed. Following recovery from surgery the cat has remained clinically normal. This report highlights the possibility of temporary SUB placement as a bridge to definitive ureteral repair in cases of accidental ureteral ligation.